PENGARUH SERVICESCAPE DAN HOSPITALITY TERHADAP IMAGE PERPUSTAKAAN UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Haloho, Elizabeth; Harefa, Hilda Syaf’aini; Sitompul, Pandapotan; Saragih, Nawary; Simangunsong, Elisabeth (Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research is to find out and analyze servicescape that has an effect on image, hospitality has an effect on image, and servicescape and hospitality have simultaneously had an effect on image on the library of the Catholic University of Santo Thomas Medan. The research method used is a quantitative descriptive research method. . The population in this study were all active students in the 2022/2023 Academic Year, totaling 6,540 people. The technique for determining the sample in this study used Propotionate Stratified Random Sampling. As for determining the number of samples (n) used is referring to the Slovin approach. From the results of calculating the number of samples used in this study, there were 98 respondents. The scale of data measurement in this study used a Likert scale. The data analysis technique used is instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test (R2). The results of the study show that (1) the servicescape variable has a positive and significant effect on the image, (2) the hospitality variable has a positive and significant effect on the image, and (3) the servicescape and hospitality variables simultaneously have a positive and significant effect on the image of the Library of the Catholic University of Santo Thomas Medan .